THE IMPORTANCE OF SOCIAL COOPERATION IN DEVELOPING PROFESSIONAL COMPETENCIES OF FUTURE TEACHERS. - Artikbayeva A.A. (Лучшие интеллектуальные исследования, 2024)
Annotation.The article analyzes the development of students' professional competencies based on social cooperation in the process of internship, their goals and objectives, their ability to assess the professional competence of university teachers and determine directions for development.